Co-operation of Edu-business and Public Schooling: Is the Governance of Education in Finland Shifting from the Public Sector to Networks? - Kiesi Iida (Springer, 2025)
The number of edu-business actors involved in Finnish schooling is increasing, as is their collaboration with the public sector. This chapter introduces concrete examples of how edu-business actors in Finland collaborate with state actors and also discusses what their aspirations are for future collaboration with state actors. By analysing these forms of co-operation and the expectations of Finnish edu-business actors, I aim to describe the current position and the course of governance of education in Finland. I argue that edu-business networks, that cross and blur the sectoral boundaries between public and private, create possibilities for edu-business actors to affect education policies in Finland. This possibility of a shift from the public governance of education towards network governance can weaken the democratic aspects of the public education system as networks lack commitment to transparent decision-making and accountability to the public.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling